1995
DOI: 10.1074/jbc.270.11.5857
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification of Two Novel Munc-18 Isoforms Expressed in Non-neuronal Tissues

Abstract: Munc-18, also known as n-Sec1 or rbSec1, is a syntaxin-binding protein thought to play a role in regulating synaptic vesicle exocytosis. Although a gene family of syntaxins has been identified, only a limited subset bind to Munc-18. This implicates the existence of other mammalian Munc-18 homologues that may be involved in a range of vesicle transport reactions. The purpose of the present study was to identify other members of the Munc-18 family by cDNA cloning. Three distinct Munc-18 isoforms, Munc-18a, previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
141
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 27 publications
5
141
0
1
Order By: Relevance
“…This is of importance, as first-phase GSIS is much reduced in patients with type 2 diabetes, and this has been attributed in part to greatly reduced islet SYN-1A levels [23], along with reduction of cognate SNAREs (SNAP25 and VAMP2) and the Sec1/Munc18-like protein (SM) Munc18a. SYN-3 was shown in pancreatic acinar cells to preferentially form complexes with VAMP8 [20] and Munc18b [38,39], which are also present in beta cells [40][41][42]. We recently reported, employing the Vamp8-knockout mice [43], that VAMP8 also mediated the recruitment and fusion of newcomer SGs, and was the putative cognate v-SNARE that binds SYN-3.…”
Section: Discussionmentioning
confidence: 99%
“…This is of importance, as first-phase GSIS is much reduced in patients with type 2 diabetes, and this has been attributed in part to greatly reduced islet SYN-1A levels [23], along with reduction of cognate SNAREs (SNAP25 and VAMP2) and the Sec1/Munc18-like protein (SM) Munc18a. SYN-3 was shown in pancreatic acinar cells to preferentially form complexes with VAMP8 [20] and Munc18b [38,39], which are also present in beta cells [40][41][42]. We recently reported, employing the Vamp8-knockout mice [43], that VAMP8 also mediated the recruitment and fusion of newcomer SGs, and was the putative cognate v-SNARE that binds SYN-3.…”
Section: Discussionmentioning
confidence: 99%
“…pcDNA3-Munc18c was constructed by subcloning a 2.5-kb EcoRI fragment from pMEXneo-Munc18c into the EcoRI site of pcDNA3 (Invitrogen) (21). The pBluescript KG-Munc18b and pRSETA-Munc18c constructs have been described (21,30). pET20b-Syntaxin4 was kindly donated by Dr. Jenny Martin (Institute of Molecular Bioscience, Brisbane, Australia).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies of recombinant proteins indeed demonstrated stable binding of VAMP-2, SNAP-23, and syntaxin-4 (22), raising the possibility that a complex of VAMP-2/ SNAP-23/syntaxin-4 could mediate basolateral exocytosis of digestive enzymes within the pancreas. Non-neuronal Munc18 isoforms were also identified, including Munc18b and Munc18c (21)(22)(23)(24)(25)(26). Munc18c binds to syntaxin-4 and blocks its binding to SNAP-23 and VAMP-2 (24,25), and overexpression of Munc18c in adipocytes inhibits insulin-mediated GLUT-4 translocation to the plasma membrane and glucose transport (26).…”
mentioning
confidence: 99%